CHARACTERISTICS OF SUFI AL-SULAMY’S TAFSIR METHOD: A CASE STUDY OF THE PROPHET OF MUSA AND KHIDIR - Muhamad Agus Mushodiq; Wahyudi Wahyudi (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2020)
This paper aims to explore the Characteristics of the Tafsir Method used by Abu 'Abdu ar-Rahman Muhammad al-Sulamy in his book Haqāiqu Tafsîr. In addition, this paper also reveals the Sufistic values ​​contained in the story of the Prophet Musa and 'Abd which are allegedly the Sufistic Story in the Quran. In conducting the research, the writer used qualitative descriptive research analytical. So that the data obtained are not only described but also analyzed. From the results of this study it is concluded that the characteristics of the al-Sulamy Tafsir Method can be concluded as follows. First, in interpreting the Quran, al-Sulamy arranged the surahs according to the order of the Usmani Manuscripts, namely from Surat al-Fatihah to Surat an-Nas by not interpreting the entire verse in the letter. Second, in several interpreted verses, al-Sulamy's interpretation style refers to the bi riwayah or naqly interpretation by quoting the ayat (verse) or hadith. Third, in quoting certain opinions, sometimes al-Sulamy did not use the bright name of the Sufi, he used the identity of a Sufi group in a certain area, for example, 'Iraqiyyin (Sufis from Iraq), Bagdadiyyin (the Sufis from Baghdad). Fourth, the methods used by al-Sulamy in interpreting verses in the Qur'an are predominantly the isyari method. Fifth. in interpreting, al-Sulamy also contributed in conveying his ideas regarding the meaning of certain verses. The Sufistic values ​​that can be concluded from the story of the Prophet Musa and 'Abd are lessons about the nature of worship which is not only oriented towards external or physical movements of worship, synergies between fiqh and Sufism in order to get closer to Allah, the prohibition of greedy and riya' , the urgency of knowing one's position in worshiping Allah SWT, the importance of having good character in knowledge, and calming the soul.